The migration theory’s process of formation and development in the globalizing world - Sheryazdanova Kamilla Galimovna, Popova Yelena Alexandrovna, (Opción, 2019)
In this article, the authors analyzed the process of formation and development of the migration theory, from the end of the XIX century to the beginning of the XXI century through the method of documentary research. As a result, the countries of origin reap the benefits of intellectual migration in the event of the return of their highly qualified personnel to their homeland. In conclusion, the labor market and the education system play the role of connecting elements between Diasporas and the local population, through which representatives of ethnic groups are built-in into the existing system of relations.